(untitled) (Research, Society and Development, 2025)
In vitro bovine embryo production (IVEP) is a biotechnological technique widely used to increase reproductive and genetic efficiency in cattle farming. The aim of this article is to review the existing literature on in vitro bovine embryo production. This article presents technical advances, challenges and perspectives in the field, based on recent studies from the last five years. Innovations in oocyte maturation, in vitro fertilization and embryo culture stand out, in addition to logistical and oocyte quality challenges. The results indicate that the integration of new technologies and the adaptation of protocols can expand the application of IVEP on a large scale. IVEP has played a crucial role in the advancement of cattle farming, allowing the production of high-quality embryos and promoting significant genetic gains. Despite the logistical and technical challenges, recent innovations offer promising solutions to expand its application, especially in remote regions.